Uji Aktivitas Antioksidan Sediaan Salep Ikan Gabus (Channa Striata) Kombinasi Vitamin C dan Madu Kelulut (Heterotrigona Itama) - Risma Dwi Anugerah; Wintari Taurina; Mohamad Andrie (Journal Syifa Sciences and Clinical Research, 2022)
Based on the results of research, snakehead fish extract and kelulut honey have properties to make wounds heal faster. Ointment with an active formulation of snakehead fish extract and extract of kelulut honey showed an oxidation process that could make the preparation rancid. The addition of BHA and Vitamin C is expected to prevent the oxidation process so that the preparation does not become rancid. This study aims to determine the effect of adding Antioxidant BHA and Vitamin C in preventing the oxidation process of the ointment in the aqueous phase of extracts of snakehead fish (Channa Striata)and of kelulut honey (Heterotrigona Itama) at 28 days storage. Stability was accelerated at a temperature of 40 ± 20ºC and a RH of 75 ± 5%. Variations in the concentration ofiBHA and Vitamin C used were BHA.0.02. : Vitamin C 0.1, BHA 0.02 : Vitamin C 0.01, BHA 0.005 : Vitamin C 0.01, and BHA 0.005 : Vitamin C 0.1 then tested the physical properties of the ointment, namely through organoleptic test, homogeneity test, spreadability test, adhesion test, protection test and acid number test which were then analyzed by SPSS. Based on the analysis of the scattering power showed a significant difference between F0, F1, and F3. The results of the adhesion analysis showed that there were significant differences in each formula. Furthermore, the results of the stability test showed that all formulas had good physical stability. Conclusion: F1 is a very good formula to prevent oxidation in the preparation as evidenced by a decreased acid number, which is 9.62 mg KOH/g.